Answer:
ur correct u got it.
Step-by-step explanation:
Answer:
![h^{-1}(x)=-\frac{3}{2}x+9](https://tex.z-dn.net/?f=h%5E%7B-1%7D%28x%29%3D-%5Cfrac%7B3%7D%7B2%7Dx%2B9)
Step-by-step explanation:
To find inverse of a function, follow the steps below:
1. replace h(x) with y
2. Interchange x and y
3. Solve for the new y
4. Replace y to
(this is the inverse function)
<u>Step 1:</u> y = -2/3x+6
<u>Step 2:</u> x = -2/3y+6
<u>Step 3:</u>
![x=-\frac{2}{3}y+6\\\frac{2}{3}y=-x+6\\y=\frac{-x}{\frac{2}{3}}+\frac{6}{\frac{2}{3}}\\y=-\frac{3}{2}x+9](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B2%7D%7B3%7Dy%2B6%5C%5C%5Cfrac%7B2%7D%7B3%7Dy%3D-x%2B6%5C%5Cy%3D%5Cfrac%7B-x%7D%7B%5Cfrac%7B2%7D%7B3%7D%7D%2B%5Cfrac%7B6%7D%7B%5Cfrac%7B2%7D%7B3%7D%7D%5C%5Cy%3D-%5Cfrac%7B3%7D%7B2%7Dx%2B9)
<u>Step 4:</u>
![y=-\frac{3}{2}x+9\\h^{-1}(x)=-\frac{3}{2}x+9](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B3%7D%7B2%7Dx%2B9%5C%5Ch%5E%7B-1%7D%28x%29%3D-%5Cfrac%7B3%7D%7B2%7Dx%2B9)
This is the inverse function.
From the expression <span>8(x +4) (y +4) (z 2 + 4z + 7),
</span>the factors are 8, (x+4), (y+4), <span>(z^2 + 4z + 7) since each of these factors, when you divide that to the whole expression won't give a remainder</span>
Answer:
106.25
Step-by-step explanation:
99.5+113= 212.5 /2 = 106.25
F(x , y) = x + y - xy, D is the closed triangular region with vertices (0, 0), (0 , 2) , and (4 , 0)